PENGEMBANGAN MEDIA KERAYA (KERAGAMAN BUDAYA) BERBASIS ASSEMBLR EDU SEBAGAI WUJUD CINTA TANAH AIR MATA PELAJARAN IPAS SISWA KELAS IV SD NEGERI 1 BANJAREJO - Dwi Nurul Fadlilah; Husni Wakhyudin; Singgih Adhi Prasetyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop KERAYA (Cultural Diversity) learning media based on the Assemblr Edu application as a form of love for the homeland for fourth-grade students of SD Negeri 1 Banjarejo. The specific objectives of this study include: 1) obtaining the validity of KERAYA media based on Assemblr Edu in science learning for fourth-grade students; 2) obtaining the feasibility of the media as a means of instilling a love for the homeland; and 3) determining the acceptance of the media by students. This study uses the Research and Development (R&D) method with the ADDIE development model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects were fourth-grade students of SD Negeri 1 Banjarejo, Blora Regency, Central Java. KERAYA media contains cultural diversity material and is based on Augmented Reality (AR) with 3D visuals, 2D images, regional songs, hyperlinks, guidebooks and QR codes for easy access. Data collection instruments include expert validation sheets, teacher validation, and student response questionnaires. Data analysis techniques focused on the validity, feasibility, and acceptability of the media. The results showed that the KERAYA media obtained a validity score of 88% (very feasible category), feasibility of 95% (very feasible category), and acceptance by students of 99% (very good category). Thus, the KERAYA learning media based on Assemblr Edu was declared very valid, very feasible, and acceptable as an effective learning media in fostering a sense of love for the homeland.